Cartilaginous predictors of residual acetabular dysplasia (RAD) in developmental dysplasia of the hip following closed or open reduction: A systematic review and meta-analysis - Yang, Shuai; Su, Fei; Jia, Hao-Ruo; Liu, Chen-Xin; Lu, Qing-Da; Yang, Ya-Ting; Liu, Yong; Wang, Jia-Ju; Jie, Qiang (Frontiers in Pediatrics, 2023)
Object This study was designed to analyze the cartilaginous predictors of residual acetabular dysplasia (RAD) after early treatment of developmental dysplasia of the hip and their diagnostic accuracy. Study design Databases such as PubMed, Embase, Cochrane, and Web of science were searched to screen the literature. The quality of the literature was assessed by the QUADAS-2 tool. Qualitative and quantitative synthesis of literature were performed based on extracted data. For quantitative synthesis studies, the sensitivity, specificity, diagnostic odds ratio (DOR), and summary receiver operating characteristic (SROC) curve with corresponding confidence intervals were calculated. Results For the cartilaginous acetabular index (CAI) group, the combined values of sensitivity, specificity, and DOR were 0.80 (95% CI = 0.54–0.93), 0.73 (95% CI = 0.57–0.84), and 10.62 (95% CI = 3.96–28.53), respectively. The corresponding values in the cartilaginous center-edge angle (CCE) group were 0.71 (95% CI = 0.57–0.82), 0.78 (95% CI = 0.66–0.87), and 8.64 (95% CI = 3.08–24.25), respectively. The area under the curve (AUC) of SROC was 0.82 (95% CI = 0.78–0.85) and 0.80 (95% CI = 0.76–0.83) for the CAI and CCE groups. The CAI group had higher sensitivity, DOR, and AUC than the CCE group. Conclusion Both of these two groups have good diagnostic accuracy, and CAI/L-AI has a little edge over CCE/L-CEA. However, there is still more research needed to determine whether they can be used as independent indications for secondary orthopedic surgery. Systematic review registration: [https://www.crd.york.ac.uk/PROSPERO/], identifier: [CRD42022338332].